2012
DOI: 10.4103/0301-4738.90493
|View full text |Cite
|
Sign up to set email alerts
|

A truly knotless technique for scleral fixation of intraocular lenses: Two-year results

Abstract: Scleral fixated intraocular lens (SFIOL) is a safe and effective option for managing optical aphakia. Suture related complications like suture erosion, suture breakage, endophthalmitis, etc. are unique to SFIOL. The knots can be covered by partial thickness flaps or they can be rotated into scleral tissues without flaps to reduce the complications. We performed a recently described novel technique which obviates the need for knot and scleral flaps in securing the SFIOL. This novel 2-point Ab externo knotless t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…No significant statistical differences were found when comparing the preoperative and postoperative BCVA values between the two groups of patients, indicating that the visual outcomes of the two groups were equal after surgery. In our study, all of the treated eyes (30/30) either maintained or improved their BCVAs, which is similar to Szurman’s original knotless suture fixation of the PCIOL method (21/22) [ 21 ], suggesting that the modified knotless method could be a potentially promising surgery technique for patients with CEL.…”
Section: Discussionsupporting
confidence: 82%
“…No significant statistical differences were found when comparing the preoperative and postoperative BCVA values between the two groups of patients, indicating that the visual outcomes of the two groups were equal after surgery. In our study, all of the treated eyes (30/30) either maintained or improved their BCVAs, which is similar to Szurman’s original knotless suture fixation of the PCIOL method (21/22) [ 21 ], suggesting that the modified knotless method could be a potentially promising surgery technique for patients with CEL.…”
Section: Discussionsupporting
confidence: 82%
“…[27] The SFIOL procedure has good visual outcomes but is known to be associated with long-term complications such as cystoid macular edema, retinal detachments, and suture-related complications. [389] Teng and Zhang compared anterior chamber implantation of iris claw lens with SFIOL and found that iris claw lens implantation can be performed less invasively, within a shorter surgical duration and is associated with faster visual recovery in comparison with SFIOL. [9] The safety and efficacy of aphakic rehabilitation with retropupillary iris claw fixation has been studied and it has been found to be a safe procedure for rehabilitation of aphakic eyes.…”
Section: Discussionmentioning
confidence: 99%
“…This has been linked to various complications including bullous keratopathy, increase of intra ocular pressure (IOP), and endothelial cell loss or even visual loss. Several techniques including posterior chamber sclera fixed lens,3,4 and anterior chamber iris claw lens5 have been reported to result in good visual outcome in the management of unilateral aphakic eyes without capsular support. Technological advances in lens design (angular support) and in lens material (Acrysoft) has permitted the safe use of lens in the anterior chamber for refractive error correction 6,7.…”
Section: Introductionmentioning
confidence: 99%